2008
DOI: 10.1080/17470910701745858
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive humor processing: Different logical mechanisms in nonverbal cartoons—an fMRI study

Abstract: Although recent fMRI studies on humor have begun to elucidate cognitive and affective neural correlates, they weren't able to distinguish between different logical mechanisms or steps of humor processing, i.e., the detection of an incongruity and its resolution. This fMRI study aimed to focus in more detail on cognitive humor processing. In order to investigate pure incongruity resolution without preprocessing steps, nonverbal cartoons differing in their logical mechanisms were contrasted with nonhumorous pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 51 publications
8
121
2
9
Order By: Relevance
“…All pictures were low in aggressive, violent, and sexual content and were validated by use in previous studies (Samson et al, 2008(Samson et al, , 2009). To investigate brain activity during resting state trials, these cartoon trials were interleaved with rest events (NULL) during which participants observed a blank screen.…”
Section: Fmri Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…All pictures were low in aggressive, violent, and sexual content and were validated by use in previous studies (Samson et al, 2008(Samson et al, , 2009). To investigate brain activity during resting state trials, these cartoon trials were interleaved with rest events (NULL) during which participants observed a blank screen.…”
Section: Fmri Taskmentioning
confidence: 99%
“…It has recently been shown that ToM cartoons (which require additional mentalising skills in order to be understood -the ability to recognise that one character portrayed in the cartoon has a false beliefrequire more involvement of so-called 'mentalising areas' [e.g., medial prefrontal cortex, temporo-parietal junction (TPJ)] in contrast to cartoons that can be understood without taking the characters' false beliefs into account (Samson et al, 2008(Samson et al, , 2009). While there is a good understanding on which regions are activated during ToM processes, no study has investigated the functional connectivity during ToM processing in BPD patients compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…LMs are of particular interest in the present study. Previous studies (Samson et al 2008;Samson 2009) showed that different LMs have different cognitive requirements which were shown to influence neural activation patterns. Visual puns (PUN, which are based on one visual element simultaneously evoking two meanings) were shown to evoke more activation in the visual cortex whereas TOM cartoons (TOM, they require additional mentalizing skills in order to be understood: it has to be recognized that one character portrayed in the cartoon has a false mental state) require more involvement of so-called ''mentalizing areas'' [e.g., medial prefrontal cortex, temporo-parietal junction (TPJ)].…”
Section: Introductionmentioning
confidence: 99%
“…It is located at the end of the superior temporal sulcus and is approximately equivalent to Brodmann´s area 19. It has also been reported to be activated in a recent fmri study on processing of noverbal cartoons [35]. We had no a-priori hypothesis regarding the fasciculus occipito-frontalis and anterior cingulate, where a negative correlation was found .…”
Section: Discussionmentioning
confidence: 75%
“…Notably, some of the regions found to be activated in these studies on personality traits were also found to be activated in brain imaging studies on humor appreciation. A number of studies have investigated the neural correlates of humor appreciation with functional magnetic resonance [3,13,14,22,24,25,35,39,43] and PET [17] (see [41] and [43] for an overview). The regions shown to be activated during humor appreciation in these studies included both cortical regions (such as the left inferior frontal gyrus [25,43], medial frontal [13], anterior [13,14,43] and posterior temporal [13,14,35] gyri) as well as subcortical nuclei (such as the caudate [14] and nucleus accumbens [17]) and limbic structures (such as the hippocampus [14] or amygdalae [24]).…”
Section: Introductionmentioning
confidence: 99%